Enzymatic synthesis of vitexin glycosides and their activity. Issue 37 (23rd August 2022) - Xu, Tingting; Fan, Ziyun; Lou, Junqiao; Du, Qi; Kong, Yue; Lu, Yujia; Wu, Xueming
Abstract : Efficient enzymatic glycosylation of vitexin in hydrophobic organic and the novel vitexin glycosides showed higher anti-tumor activities. Abstract : Vitexin is an active component of many traditional chinese medicines, and is found in various plants. The low solubility of vitexin limits its pharmaceutical usage. In this study, solvent-stable β-fructosidase was used to glycosylate vitexin in organic solvents. The β-fructosidase showed high activity and stability in 30–80% (v/v) ethyl acetate with 90–99% yields of vitexin glycosides. Highly efficient synthesis of β-d -fructofuranosyl-(2→6)-vitexin (1.04 g L −1 ) and β-d -difructofuranosyl-(2→6)-vitexin (0.45 g L −1 ) was attained in 50% (v/v) ethyl acetate solvent system from 1.5 g L −1 vitexin. Two novel vitexin glycosides showed higher anti-tumor activities compared to that of vitexin by employing a human breast cancer cytotoxicity assay.